Classification of finite commutative semigroups for which the inverse monoid of local automorphisms is permutable - Derech, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We give a classification of finite commutative semigroups for which the inverse monoid of local automorphisms ispermutable.